Research on Composite Continuously Variable Transmission of Double Variable Diameter Pulley and Planetary Transmission - Yan Chuang; Song Aiping; Pan Jianzhou; Huang Jiaming (Jixie chuandong)
In order to obtain different working speeds under different conditions, the required output speed can change evenly within a certain range, so that the speed and power output can reach a better balance point, so as to reduce energy consumption. At this time, it is necessary to use continuously variable transmission (CVT). At present, most CVT devices on the market can achieve a small speed range, which is insufficient in the case of large-span transmission. A high-efficiency long-span continuously variable transmission is studied, a long-span transmission ratio cone disc composite continuously variable transmission is proposed, the torque and speed formula of this new type of transmission are deduced, and the maximum span ratio of the continuous variation range of output speed is obtained. The power transmission path of this new transmission is analyzed, and an efficient power transmission path is obtained. The transmission has the characteristics of high transmission power, high transmission efficiency and wide transmission ratio span.